Friend or foe? Attitudes of rice farmers toward wild animals in West Africa - Patrícia Chaves; Marije Schaafsma; Djunco Dabo; Judite Z. Lomba; Fode Mane; Ricardo F. de Lima; Jorge M. Palmeirim; Ricardo Rocha; Sambu Seck; Justino Biai; Sérgio Timóteo; Christoph F. J. Meyer; et al. (Ecology and Society)
As the global human population grows and the demand for space and resources increases, human-wildlife interactions and conflicts are expected to rise, particularly in biodiversity-rich tropical agroecosystems where subsistence farmers and wildlife coexist. We investigated farmers' attitudes using the ABC framework, analyzing their affect, behavior, and cognition toward wild animals. Additionally, we explored how socio-demographic characteristics influence farmers’ attitudes. Through individual interviews and focus groups, we assessed the responses of farmers from six villages in the Oio region of Guinea-Bissau, West Africa. Most farmers (56%) expressed positive emotions toward rice production, which is solely for subsistence, despite facing challenges such as animal pests (87%) and inadequate tools (78%). Farmers showed strong knowledge of local wildlife at the class level. However, even when 'bird' and 'bat' were accepted as correct, identification accuracy at lower taxonomic levels varied between 67.5% and 80.4% across different villages. Farmers have mixed emotions about wild animals, with a general tendency toward negative feelings due to crop damage (49%) and human harm (20%), while positive feelings are tied to cultural beliefs (51%), harmlessness (7%), proximity to water (4%), and edibility (4%). Although attitudes toward animals varied between villages, respondent age and education did not seem to affect these views. Wildlife crop protection behaviors were consistent across villages but varied by target animal. Most strategies were non-lethal, such as making noise (44%) or guarding fields (12%), but a common perception of their ineffectiveness may explain resistance to promoting beneficial animals in their fields. When asked about having beneficial animals in their fields, 89% of farmers either did not know or chose not to answer. These findings highlight the complex relationship between smallholder rice farmers and wildlife in developing regions. Understanding these dynamics is crucial for fostering coexistence and promoting both biodiversity and sustainable agriculture.